1999
DOI: 10.1046/j.1365-2982.1999.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Motility in the Roux‐Y limb after distal gastrectomy: relation to the length of the limb and the afferent duodenojejunal segment – an experimental study

Abstract: Following gastrectomy, the longer is a Roux-Y limb constructed to restore digestive continuity the higher the frequency of postoperative symptoms. The aim of this experimental study was to test how the level of the jejunal transection and the length of the Roux limb affect the motility of the constructed limb and in particular the onset and the propagation of activity fronts (AFs). Three months after a distal Roux-en-Y gastrectomy, electromyographic tracings were recorded in six groups of rats grouped accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In ten patients subject to Roux‐en‐Y with a total gastrectomy (cancer being the main indication), a mean small intestinal transit for solids of 293 ± 37 min was observed as compared with 187 ± 37 min in five controls ( P < 0.02), thus suggesting the small intestinal transit to be increased post RYGB [50] . Animal models of RYGB surgery suggested a similar impact of surgery as that observed in man, with disturbed small intestinal motility reported in rat and dog [54–56] …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In ten patients subject to Roux‐en‐Y with a total gastrectomy (cancer being the main indication), a mean small intestinal transit for solids of 293 ± 37 min was observed as compared with 187 ± 37 min in five controls ( P < 0.02), thus suggesting the small intestinal transit to be increased post RYGB [50] . Animal models of RYGB surgery suggested a similar impact of surgery as that observed in man, with disturbed small intestinal motility reported in rat and dog [54–56] …”
Section: Resultsmentioning
confidence: 59%
“…[50] Animal models of RYGB surgery suggested a similar impact of surgery as that observed in man, with disturbed small intestinal motility reported in rat and dog. [54][55][56] Two scenarios were created with regards to small intestinal transit time. In the first scenario the transit time was assumed [40][41][42][43] 200…”
Section: Small Intestinal Motility and Transit Timementioning
confidence: 99%
“…They employed a sequential scintigraphic HIDA Tc 99m research that demonstrated the absence of biliary reflux in the stomach remnant 12 . Le Blanc-Louvry et al 13 , reported that it is necessary to compare a short Roux limb that presents only a mild motor impairment, but allows that the enterobiliopancreatic juice flows back into the stomach, to a long Roux limb with significant motor impairment, but protects the stomach from the reflux.…”
Section: Discussionmentioning
confidence: 99%
“…An additional issue to consider is liquid stasis in the gastric remnant after Roux‐en‐Y reconstruction for distal gastrectomy . We performed gastrojejunostomy for functional end‐to‐end anastomosis to create a straight entry to the Roux‐en‐Y limb and to avoid making an angle or a stricture just after the anastomosis.…”
Section: Discussionmentioning
confidence: 99%